THE INFLUENCE OF PERCEIVED EASE OF USE, CHALLENGE, VARIETY, AND SOCIAL INTERACTION ON PERCEIVED ENJOYMENT IN ROBLOX - Liliana Dewi; Rachel Naomi Supratman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The rapid growth of the global gaming industry has intensified competition among digital game platforms, making user enjoyment a critical factor for sustained engagement. Roblox, as a large-scale user-generated gaming platform, offers diverse gameplay experiences and social interactions that may influence users’ perceived enjoyment. This study aims to examine the influence of perceived ease of use, challenge, variety, and social interaction on perceived enjoyment among Roblox users. A quantitative research approach was employed using an online survey distributed to respondents aged 12–30 years who had prior experience playing Roblox. A total of 190 valid responses were analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that perceived ease of use, variety, and social interaction have significant positive effects on perceived enjoyment, while challenge does not show a significant influence. These findings suggest that enjoyment in a user-generated gaming platform is driven more by usability, content diversity, and social engagement than by perceived difficulty. The study contributes to the understanding of user experience in digital gaming platforms and provides practical implications for developers and content creators in designing strategies to enhance player enjoyment and long-term engagement.